Anti-Obesity Effect Of Mushroom (Ganoderma Lucidum) On Experimentally Induced Obese Rats (Anwer Khan Modern Medical College Journal, 2012)
This experimental study was done to determine whether Ganoderma Lucidum (GL), a renowned  medicinal species, has an effect on body weight in an obese animal model induced by the  administration of a fatty mixture diet. The study was carried out in the department of Pharmacy,  Jahangirnagar University and National Mushroom Development and Extension Center  (NAMDEC) with 36 rats were divided into 3 groups as follows. The Control group (C) received  normal/basal laboratory diet, experimental group (E) was fed fatty mixture diet and mushroom  fed group (M) received 5% powder of GL with fatty mixture for 28 days. 5% powder of GL  administration significantly reduced body weight in obese rats than group E. The present study  suggests that GL may serve as a new potential natural product for the prevention of obesity. DOI: http://dx.doi.org/10.3329/akmmcj.v3i2.11687 AKMMC J 2012: 3(2): 11-14